Eskalasi Kekerasan Berbasis Gender Online Di Masa Pandemi: Studi Penanganan Kasus Pornografi - Hany Areta A; Hardiana Clarisa; Siti Chatlia Q (Universitas Islam Indonesia, 2021)
This legal research aims to optimize the handling of Non-Consensual Dissemination Of Intimate Images in the context of realizing a just law by revising the explanations of Article 4 paragraph (1) and Article 6 of the Pornography Law (